Analisis Perbandingan Kinerja Keuangan Bank di Indonesia Sebelum dan pada Saat Pandemi Covid-19: Studi Kasus pada Bank BUMN Periode 2018-2021 - Fitri Azzahra Raharja; Niswatin; Ronal S. Badu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The quick of the Covid-19 virus across all countries, including Indonesia, has led banking in Indonesia to experience challenges in its development. In this case, Indonesia banks must maintain their financial performance as it could affect the bank health level. Financial performance analysis was used as a benchmark for assessing banking financial performance. This research aimed to analyze and examine differences in the financial performanceof State-Owned Banks (BUMN) before and during Covid-19 by using CAR, ROA, BOPO, and NPL ratios. The research employed a quantitative approach. The findings indicated a significant difference in the ROA, ratio, which meant that H2 was confirmed, and no sicnificant difference in the CAR, BOPO, and NPL ratio was found, meaning that H1, H3 and H4 in this researchweare rejected.